2020
DOI: 10.1007/s10494-020-00169-3
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Gradient and Strain Rate Statistics in Oblique Premixed Flame–Wall Interaction Within Turbulent Channel Flows

Abstract: Three-dimensional direct numerical simulations of V-flames interacting with chemically inert walls in a fully developed turbulent channel flow have been performed under adiabatic and isothermal wall boundary conditions using single-step chemistry. These simulations are representative of stoichiometric methane-air mixture at unity Lewis number under atmospheric conditions. The turbulence in the non-reacting channel is representative of the friction velocity based Reynolds number $$Re_{\tau }=110$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 86 publications
2
27
0
Order By: Relevance
“…In particular, isothermal and adiabatic walls provide qualitatively different flame shapes. Such a result agrees with the recent findings of Ahmed et al [23,24], who also found that the shapes of the oblique premixed turbulent flame fronts in the near-wall region differ for the isothermal and adiabatic walls; see Reference [24] and references therein for more details.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In particular, isothermal and adiabatic walls provide qualitatively different flame shapes. Such a result agrees with the recent findings of Ahmed et al [23,24], who also found that the shapes of the oblique premixed turbulent flame fronts in the near-wall region differ for the isothermal and adiabatic walls; see Reference [24] and references therein for more details.…”
Section: Resultssupporting
confidence: 92%
“…These interactions occur in many engineering applications such as spark-ignition engines, gas turbines, etc., with the walls playing an important role in the formation of the turbulent structures and, consequently, in the combustion process. Ahmed et al [23,24] investigated the interaction of oblique flames with adiabatic and isothermal walls by performing the DNS of the V-shaped flames developed in a channel flow. Additionally, the V-flame in the adiabatic case presented the features of the aerodynamic quenching.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in hybrid engines) are now made smaller in size and increased popularity of microcombustors has increased the importance of premixed flame-wall interactions for combustion modellers. Recent analyses on turbulent premixed flame-wall interaction suggest that the decrease in dilatation rate either due to flame quenching as a result of wall heat loss or due to wall-induced confinement can have a significant influence on enstrophy (Lai et al 2017a), turbulent kinetic energy (Lai et al 2017b;Ahmed et al 2019c), turbulent scalar flux (Lai et al 2017c), scalar variance (Lai and Chakraborty 2016a) and reactive scalar gradient statistics (Sellmann et al 2017;Lai and Chakraborty 2016b, c, d;Ahmed et al 2020;Bruneaux et al 1997) in the near-wall region. Moreover, the usual log-law for mean velocity and temperature variations is often rendered invalid during turbulent premixed flame-wall interactions (Bruneaux et al 1997(Bruneaux et al , 1996Jainski et al 2018).…”
Section: Final Remarks and Outlookmentioning
confidence: 99%